Interpretative Flexibility of Digital Immigrant Towards Ajaib Stock Trading Application - Afifah, Sayyidah; Yuliawati, Elly (Universitas Wiralodra, 2024)
The Digital Immigrant as users of financial technology, particularly Ajaib Stock Application represent a group that has witnessed the inception and evolution of digital technology, typically lacking proficiency in operating modern technological tools. This study aims to uncover the interpretative flexibility of Digital Immigrants in their experience of using the Ajaib application. The research is grounded in the Social Construction of Technology theory, Phenomenological theory, and Social Category theory. The paradigm of this research adopting a constructivist, the research approach using a qualitative approach, utilizing phenomenological research methods. Data collection techniques used in this study by semi-structured interviews and literature studies. The study reveals that Digital Immigrants demonstrate interpretative flexibility in navigating the Ajaib application amidst the challenges posed by the Covid-19 pandemic. The diversity of interpretative flexibility is based on the various initial motives for using the application, categorized into motives 'because of' and 'in order to'. These motives influence interpretative flexibility concerning language, usage, and structure. Additionally, the interpretative flexibility of digital immigrants is intertwined with a wider context, reflecting various challenges encountered while engaging with the Ajaib application.